Stem cells origin and migration - Montiel-Eulefi, E; Montiel, J (2012)
Generation, migration and distribution of stem cells throughout the body are a major process in the generation of morphological divergence and evolution in different species of vertebrates. Progenitor cells pass through different compartments during embryonic development and the exposition to different tissue environments stimulates the activation of specific differentiation programs. In this chapter we discuss the origin of different migratory cell populations, such as embryonic stem cells, primordial germ cells and neural crest cells, with focus on the different molecular factors activated during migration to different embryonic compartments.